Jacqueline Woodson's narrative style in The Other Side: An African American picture book for children - lvalue lvalue (Universitat Jaume I. Department of English Studies, 2019)
Author/s Agustín Reyes Torres Universitat de València, Spain   ABSTRACT The Other Side (2001) is a children's story with multicultural characters and themes that can be regarded as an aesthetic exploration of the human experience in the process of the acquisition of knowledge. Following the Black Arts Movement, Jacqueline Woodson's work portrays many of the issues that are present in the real world but seldom appear in children's literature, such as racial division or interracial relationships. Using the metaphor of a fence, this African American author reveals issues of loneliness and friendship, inclusion and exclusion, and the overcoming of prejudice and segregation through the wisdom of Clover and Annie, an African American and a white girl, who become friends. The story is told from the point of view of Clover who is both the protagonist and the first person narrator. The reader, thus, gets to see and understand the world through her eyes.